Pengembangan E-Modul Pola Busana Cad dengan Software Richpeace pada Mata Kuliah Pembuatan Pola dengan Komputer - Ramadhani, Yashinta; Sholikhah, Roudlotus; Wahyuningsih, Sri Endah; Atika, Atika (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2024)
Abstract: Media is an important component in achieving learning objectives, as well as in the Computer Aided Pattern Making which studies CAD clothing pattern making using Richpeace software. This is a Research and Development (R&D) of analyzing the procedures and feasibility results of e-module development by testing the product results to expert judgment in the form of material experts and media experts. Methods of data collection using documentation and observation techniques. The development method takes the 5 Steps of Using the Research and Development Method from Sugiyono which consists of potentials and problems, data collection, product design, validation and revision. Based on the research that has been developed according to the procedure, the results are obtained in the form of an e-module as a way out of the problems that exist in the Computer Pattern Making Course. Assessment by material experts obtains an average proportion of 97.02% and is classified in the